Effect of Water Restriction and Supplementary Nitrogen on the Growth Dynamics of Bromus valdivianus Phil - López IF; Rodríguez A; Cartmill AD; Dörner J; Calvache I; Balocchi O (MDPI (Basel, Switzerland), 2025)
Decreasing summer precipitation is negatively affecting global productivity of grassland plant species. This study evaluated the effect of three levels of soil plant available water [80–90% PAW-H (high), 50–60% PAW-M (medium), and 20–30% PAW-L (low), which were soil water restriction (SWR) equivalent to (v/v%) 10–20%, 40–50%, and 70–80%, respectively] and nitrogen (N 0 and 110 kg ha−1) on growth and nutritional quality of Bromus valdivianus Phil. (Bv) mini-swards (MS; 125 L containers), arranged in three blocks. Total lamina length (TLL), leaf expansion rate (LER; cm d−1), phyllochron (Phy) expressed as “days” and “°C day”, tiller mass (TM, g tiller−1), number of live leaves (NLL), number of dead leaves (NDL), and accumulated herbage mass [AHM, g DM (dry mass) m2] were measured. Defoliation events, leaving 5 cm residual height, were carried out every 320 GDD (using a base growth temperature of 5 °C), and foliage samples for nutritive quality [DM, crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), water-soluble carbohydrates (WSC), and metabolic energy (ME)] were collected. Reducing PAW to 20–30% decreased the AHM by 60.7%, TLL by 52.7%, LER by 50%, and TM by 50%, with significant interaction between the main effects for AHM, TLL, and LER. The addition of N increased the AHM by 31.6%, LER by 21.6%, and TLL by 19.6%. The Phy remained undisturbed by decreasing PAW and increasing the N rate. Nutritive quality was generally not statistically different for the interaction or between N levels. However, low PAW levels resulted in statistically (p < 0.05) lower ME and higher concentrations of NDF. In general, growth, AHM, and nutritional quality of Bv during the summer period were driven by PAW levels and by the availability of N. Plant available water levels of 50% to 60% at 20 cm soil depth, with the addition of N, allowed Bv to reach its highest production.
Keywords: abiotic stress; drought; pasture brome; soil fertility